Mutant p53: a novel target for the treatment of patients with triple‐negative breast cancer?. Issue 1 (24th September 2016) - Synnott, N.C.; Murray, A.; McGowan, P.M.; Kiely, M.; Kiely, P.A.; O'Donovan, N.; O'Connor, D.P.; Gallagher, W.M.; Crown, J.; Duffy, M.J.
Abstract : The identification and validation of a targeted therapy for patients with triple‐negative breast cancer (TNBC) is currently one of the most urgent needs in breast cancer therapeutics. One of the key reasons for the failure to develop a new therapy for this subgroup of breast cancer patients has been the difficulty in identifying a highly prevalent, targetable molecular alteration in these tumors. Recently however, the p53 gene was found to be mutated in approximately 80% of basal/TNBC, raising the possibility that targeting the mutant p53 protein product might be a new approach for the treatment of this form of breast cancer. In this study, we investigated the anti‐cancer activity of PRIMA‐1 and PRIMA‐1 MET (APR‐246), two compounds which were previously reported to reactivate mutant p53 and convert it to a form with wild‐type (WT) properties. Using a panel of 18 breast cancer cell lines and 2 immortalized breast cell lines, inhibition of proliferation by PRIMA‐1 and PRIMA‐1 MET was found to be cell‐line dependent, but independent of cell line molecular subtype. Although response was independent of molecular subtype, p53 mutated cell lines were significantly more sensitive to PRIMA‐1 MET than p53 WT cells ( p = 0.029). Furthermore, response (measured as IC50 value) correlated significantly with p53 protein level as measured by ELISA ( p = 0.0089, r= −0.57, n = 19). In addition to inhibiting cell proliferation, PRIMA‐1 MET induced apoptosis and inhibited migration in a p53 mutant‐dependent manner. Based on our data, we conclude that targeting mutant p53 with PRIMA‐1 MET is a potential new approach for treating p53‐mutated breast cancer, including the subgroup with triple‐negative (TN) disease. Abstract : What's new? There is an urgent need for new therapies that specifically target triple‐negative breast cancer (TNBC). Surprisingly, about 80% of basal/TNBCs have recently been found to carry mutations in the p53 gene. A number of novel compounds can restore normal p53 activity. In this study, the authors found that one of these compounds, called PRIMA‐1 MET, can inhibit proliferation and migration, and induce apoptosis, in TNBC cells in vitro . These results suggest that PRIMA‐1 MET might offer a potential new therapeutic approach for treating p53‐mutated breast cancers, including TNBCs.